2014
DOI: 10.3386/w20348
|View full text |Cite
|
Sign up to set email alerts
|

How Does Family Health Care Use Respond to Economic Shocks? Realized and Anticipated Effects

Abstract: Families in constrained economic circumstances resulting from economic shocks face difficult choices regarding how best to spend their diminished resources. As families strive to preserve their living standards, decisions regarding health care use and its allocation among family members may become more discretionary and complex. Using two-year panel data from the Medical Expenditure Panel Survey for 2004 to 2011, we examine how the intra-family allocation of health care spending responds to realized and antici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Fletcher and Frisvold (2009) found that increased education yields greater use of preventive health care services which may, by implication, yield short-term increases in medical spending but avoid additional expenditures over the longer-term. By contrast, Lleras-Muney and Glied (2008) found that more educated individuals are more likely to take advantage of new 4 For example, Monheit, Grafova, and Kumar (2017) find that the poor health status of parents reduces the level of health care spending allocated to children and the share of family health spending on behalf of children. 5 In his theoretical framework for the pure investment model, increased education leads to a reduced demand for medical care if the absolute value of the inverse elasticity of the marginal product of healthy days with respect to changes in health capital is less than one.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Fletcher and Frisvold (2009) found that increased education yields greater use of preventive health care services which may, by implication, yield short-term increases in medical spending but avoid additional expenditures over the longer-term. By contrast, Lleras-Muney and Glied (2008) found that more educated individuals are more likely to take advantage of new 4 For example, Monheit, Grafova, and Kumar (2017) find that the poor health status of parents reduces the level of health care spending allocated to children and the share of family health spending on behalf of children. 5 In his theoretical framework for the pure investment model, increased education leads to a reduced demand for medical care if the absolute value of the inverse elasticity of the marginal product of healthy days with respect to changes in health capital is less than one.…”
Section: Previous Researchmentioning
confidence: 99%
“… For example, Monheit, Grafova, and Kumar () find that the poor health status of parents reduces the level of health care spending allocated to children and the share of family health spending on behalf of children.…”
mentioning
confidence: 99%
“…2 Further available evidence suggests that infant mortality in the US is pro-cyclical(Dehejia and Lleras- Muney, 2004), and being born during a recession improves childhood health in Western Europe(Angelini and Mierau, 2014). Recent evidence from the US however suggests differential effects depending on household type, finding that income shocks experienced due to the Great Recession affected health expenditure on children in single-mother families but not dual-parent households(Monheit et al 2018).…”
mentioning
confidence: 99%
“…Chapter 5 highlights the impact of income and asset losses on the households' ability to seek healthcare services. When households are economically constrained by shocks, they are faced with difficult choices and have to prioritise their resources for spending on critical needs (Monheit, 2014). Most Kenyan households have experienced shocks within a span of 5 years, with rural households experiencing higher incidence (68.7%) of shocks, relative to urban households (53.4%).…”
Section: 2mentioning
confidence: 99%
“…Negative shocks are shown to have an effect on healthcare access for households with limited or no financial protection (Baulia, 2018). When confronted by economic shocks, households' decisions regarding healthcare use become far more discretionary and complex, given they are faced with dilemmas about spending their limited resources (Monheit, 2014). Developing countries are challenged with implementing mechanisms that ensure equitable access to effective health interventions and protect their citizens against health and income shocks (Gottret & Schieber, 2006).…”
Section: Introductionmentioning
confidence: 99%